De novo production of diverse intracellular antibody libraries. - Tanaka, T; Chung, G; Forster, A; Lobato, M; Rabbitts, T (2003)
Many therapeutic targets are intracellular proteins and molecules designed to interact with them must effectively bind to their target inside the cell. Intracellular antibodies (intrabodies) recognise and bind to proteins in cells and various methods have been developed to produce such molecules. Intracellular antibody capture (IAC) is based on a genetic screening approach and is a facile methodology with which effective intracellular antibodies can be obtained. During the development of the IAC technology, consensus immunoglobulin variable frameworks were identified which can form the basis of intrabody libraries for direct screening. In this paper, we describe the de novo synthesis of intrabody libraries based on the IAC consensus sequence. The procedure comprises in vitro production of a single antibody gene fragment from oligonucleotides and diversification of CDRs of the immunoglobulin variable domain by mutagenic PCR. Completely de novo intrabody libraries can be rapidly generated in vitro by these approaches. As an example, a single immunoglobulin VH domain intrabody library was screened directly in yeast with an oncogenic BCR-ABL antigen bait and distinct antigen binders were isolated illustrating the functional utility of the library. This second generation IAC approach (IAC2) has many practical advantages, in particular the ability to isolate intrabodies by direct genetic selection, which obviates the need for in vitro production of antigen for pre-selection of antibody fragments.